(untitled) (Veterinary Science, 2017)
The Sierra Grande area, in the province of Río Negro, Argentina, has been particularly affected by trichinelosis, which remains locally endemic. In the year 2000 a descriptive study was designs to recognize the natural history of trichinosis in the area and over the period 2001-2007 a control program was carried out with identification of pigs, initial detection of infected pigs using serology (screening using ELISA and confirmation using Western blot). Initial results (2001/02) showed that out of 179 pigs studied, 36 (20,1%) were positive. In 2007 169 pigs were studied from the 14 existing breeding farms and only 2 (0,7%) were found to be positive. No cases of trichinella wereproduced in humans during the working period